EVALUASI KARAKTERISTIK KRIM EKSTRAK KUNYIT (Curcuma domestica Val.) PADA BERBAGAI FORMULASI - Simangunsong, Freddy Marthin Putra; Mulyani, Sri; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
This study aims to: 1) determine the effect of formulations on cream characteristics, 2) determine the formulations that produce the cream with the best characteristics. The experiments using Randomized Block Design consisted of 5 treatments and were grouped into 3. The cream was stored for 6 weeks and observed every 2 weeks, the 6 th week data was tested with analysis of variances, followed by Duncan test. The variables observed were homogeneity, separation ratio, dispersion, stickiness, pH, viscosity, antioxidant capacity. The results of the cream research at 6 weeks were: the treatment had an effect on the spread, viscosity, adhesiveness, pH of cream at 6 weeks, but had no effect on antioxidant activity. During the storage of the cream remains homogeneous and does increase the separation of cream (F = 1), there is an increase in dissolved power and pH but the adhesion, viscosity, and antioxidant activity decreases. The best results are the first formulation (F1) characteristics: homogeneous creams and no separation (F = 1), 4,08 cm spread, 40.758 cp viscosity, 16.2 seconds adhesiveness, IC50 antioxidant activity: 48.39 ?g / mL and pH 8.17. Keywords: turmeric extract, stability, cream, formulation, antioxidants, IC50